2016
DOI: 10.1111/mmi.13401
|View full text |Cite
|
Sign up to set email alerts
|

Concerted action of NIC relaxase and auxiliary protein MobC in RA3 plasmid conjugation

Abstract: Summary Conjugative transfer of the broad‐host‐range RA3 plasmid, the archetype of the IncU group, relies on the relaxase NIC that belongs to the as yet uncharacterized MOBP4 subfamily. NIC contains the signature motifs of HUH relaxases involved in Tyr nucleophilic attack. However, it differs in the residue involved in His activation for cation coordination and was shown here to have altered divalent cation requirements. NIC is encoded in the mobC‐nic operon preceded directly by oriT, where mobC encodes an aux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Several auxiliary proteins of conjugative plasmids of Gram- origin are described to contain a RHH motif. These include, TraY and TraM of F plasmid, TrwA of R388, VirC2 of Agrobacterium tumefaciens , NikA of R64, TraJ of RP4, MobC of RSF1010, MbeC of ColE1, MobC of RA3 ( Bowie and Sauer, 1990 ; Zhang and Meyer, 1997 ; Moncalian and De la Cruz, 2004 ; Ragonese et al, 2007 ; Yoshida et al, 2008 ; Lu et al, 2009 ; Varsaki et al, 2009 ; Godziszewska et al, 2016 ). For some of them structure-based mutational analyses have demonstrated the importance of the RHH motif in oriT binding as well as relaxase recruitment ( Yoshida et al, 2008 ; Lu et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several auxiliary proteins of conjugative plasmids of Gram- origin are described to contain a RHH motif. These include, TraY and TraM of F plasmid, TrwA of R388, VirC2 of Agrobacterium tumefaciens , NikA of R64, TraJ of RP4, MobC of RSF1010, MbeC of ColE1, MobC of RA3 ( Bowie and Sauer, 1990 ; Zhang and Meyer, 1997 ; Moncalian and De la Cruz, 2004 ; Ragonese et al, 2007 ; Yoshida et al, 2008 ; Lu et al, 2009 ; Varsaki et al, 2009 ; Godziszewska et al, 2016 ). For some of them structure-based mutational analyses have demonstrated the importance of the RHH motif in oriT binding as well as relaxase recruitment ( Yoshida et al, 2008 ; Lu et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It poses an alpha-helical structure and resembles the CB domain of bacteriophage TR integrases. Both MpsA and MpsB are indispensable for CT and MpsA most likely binds DNA through MpsB [ 23 ]. No mpsB equivalent genes were identified in pIGRK and pCW3, suggesting that MobK and TcpM bind DNA differently.…”
Section: Resultsmentioning
confidence: 99%
“…The authors speculated that TcpM could recognize DNA sequences with a partial identity to pCW3 oriT . Alternatively, additional accessory protein(s), interacting with TcpM, is (are) needed to increase TcpM (as well as pIGRK MobK) specificity [ 23 , 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies on plasmid RA3, the archetype of the IncU group, have revealed that this conjugative, low-copy-number, broad-host-range plasmid has a mosaic modular structure with functional modules intertwined by the global regulatory network ( 24 , 28 31 , 81 ). The present project focused on the expression of the RA3 stability module, comprising a unidirectionally transcribed set of ten ORFs split apparently into five differently regulated operons ( 24 ).…”
Section: Discussionmentioning
confidence: 99%